1994
DOI: 10.1111/j.1574-6968.1994.tb07265.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of proteinase inhibitors on the growth and differentiation ofTrypanosoma cruzi

Abstract: Three proteinase inhibitors, one peptidyl acyloxymethyl ketone (AMK), Z-Phe-Lys-CH2-OCO-(2,4,6-Me3)Ph.HCl, and two diazomethyl ketones (DMKs), Z-Phe-Phe-DMK and Z-Phe-Ala-DMK, have been studied for their effects in vitro on the four developmental stages of Trypanosoma cruzi. The three inhibitors penetrated living parasites and inhibited the major cysteine proteinase, cruzipain. The AMK was the most potent inhibitor of cruzipain itself and at 20 microM caused lysis of epimastigotes and trypomastigotes. When at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(28 citation statements)
references
References 14 publications
0
28
0
Order By: Relevance
“…Parasite proteinases are attractive targets for drug design due to their key role in the parasite life cycles, as proved by the effects of inhibitors on the parasite's growth and differentiation, and in the pathogenesis of the diseases in host organisms, including humans. This has been shown for parasitic protozoa, ranging from Entamoeba histolytica [34], Plasmodium fidciparum [35], T. congolence [33] to T. cruzi [9]. Therefore, the data presented here may be of significance for the design of new compounds as possible therapeutic agents for the treatment of Chagas' disease.…”
Section: Kinetic Measurementsmentioning
confidence: 52%
See 1 more Smart Citation
“…Parasite proteinases are attractive targets for drug design due to their key role in the parasite life cycles, as proved by the effects of inhibitors on the parasite's growth and differentiation, and in the pathogenesis of the diseases in host organisms, including humans. This has been shown for parasitic protozoa, ranging from Entamoeba histolytica [34], Plasmodium fidciparum [35], T. congolence [33] to T. cruzi [9]. Therefore, the data presented here may be of significance for the design of new compounds as possible therapeutic agents for the treatment of Chagas' disease.…”
Section: Kinetic Measurementsmentioning
confidence: 52%
“…Cruzipain may be involved in the defense mechanism of the parasite against the host immune response, both by hydrolyzing the Fc moiety of antibodies [7] and by participating in the penetration of the trypomastigote into the mammalian cell [8]. Recent studies with inhibitors have shown its relevance in the differentiation steps of the parasite's life cycle [9].…”
Section: Introductionmentioning
confidence: 99%
“…(1), [10,13,15,28,29; see 4 for review]. Lalmanach and co-workers [30] used the cystatin-based synthetic substrates [21] to develop peptidyl diazomethane inhibitors, far more specific for cruzipain than any tested so far.…”
Section: Cruzipainmentioning
confidence: 99%
“…Cruzipain is differentially expressed in the four main stages of the biological cycle of the parasite, its activity in epimastigotes usually being several fold higher than in the other parasite forms [14,15]. The bulk of the enzyme is lysosomal, including an epimastigotespecific, pre-lysosomal organelle called 'reservosome' [16], but there are isoforms associated to the plasma membrane [17], and some seem to be excreted into the medium [18].…”
Section: Cruzipainmentioning
confidence: 99%
“…Previous studies showed that inhibition of cruzipain pharmacologically (74) or by overexpression of the natural endogenous inhibitor chagasin (75) arrested parasite differentiation in vitro. To address the potential that TcOGNT2myc might act by such a mechanism, the localization of TcOGNT2myc was investigated by confocal immunomicroscopy.…”
Section: Fig 2 Enzymatic Activities Of Tcognt2myc Expression Strainsmentioning
confidence: 99%